RISIKO INVESTASI, BID-ASK SPREAD, DAN COST OF EQUITY CAPITAL DI PASAR MODAL INDONESIA - Agus Haryono; Edi Subiyantoro (University of Merdeka Malang, 2014)
A number of studies investigated how financial information affected investment decisions. The study extendedthis line of research by examining the effect of risk, proxied by price per share, number of shareholders, numberof dealers, trading volume, accounting risk and market risk measures on the bid ask spread. Further, theresearch tried to test the relationship between bid ask spread and cost of equity capital. The samples of thisresearch were the manufacturing companies listed at Indonesian Stock Exchange which shared the dividendfor 3 years; there were 40 companies. Data analysis technique used multiple regression analysis. The results ofregression provided evidence of statistically significant effect of price per share, market value, asset size andprice variability on bid ask spread. At last, there was a positive relationship between bid ask spread and cost ofequity capital